Project management for engineers - Rosenaud, Milton D., Jr. (Van Nostrand Reinhold New YorkUS, 1984)
Aims to equip the trained but inexperienced engineer with detailed tools that can be applied to his first or next project. Divides the management of engineering projects into 5 general managerial activities viz. defining the project; planning; leading; monitoring and completing; Stresses the importance of satisfying constraints of performance specifications, schedule, and budget. Discusses the following topics under 5 divisions viz. starting the successful project: negotiating and writing contracts; why and how to plan; organizing the project and its team: the role of the project manager; monitoring tool; reviews of projects, project cost reports, problem solving and how to complete projects.